PENGARUH MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) TERHADAP HASIL BELAJAR FISIKA PADA MATERI POKOK KALOR SISWA KELAS X SMA NEGERI - Mutiara Siagian (Program Studi Pendidikan Fisika, Institut Pendidikan Tapanuli Selatan, 2024)
The aim of this research was to know wheater there was a significant influence of using Contextual Teaching and Learning (CTL) model on students’ achievement in heat subject at the tenth grade students of SMA Negeri . The approach of this research was experimental method. Population of this reseacrh was all the tenth grade students of SMA Negeri which include 128 students or 3 classes. The sampling technique was random technique sampling, so the sample was 42 students. In collecting the data, the writer used test and questionnaire. The data was analyzed two ways. They are descriptive analysis and inferential statistics. Based on the descriptive analysis, the average of using CTL model in heat was 2.88, it was categorized “good”. Students’ achievement in heat subject before using CTL model had score 65.6, it was categorized “enough”. Students’ achievement in heat subject after using CTL model had score 72,2 it was categorized “good”. Based on statistics inferential statistic, it could be gotten that tcount=7.45 significant error level 5%, significant confidence level 95%, df = N – 2 = 42-2 = 40, it could be found that ttable= 1.68. It could be seen that tcount was graeter ttable (7.45 >1.68). It means, the alternative hypothesis was accepted. In the other words, there was a significant influence of using CTL model on students’ achievement in heat subject at the tenth grade students of SMA Negeri.